Distance-to-target weighting factor sets in LCA for China under 2030 vision. (10th September 2021) - Miao, Jingyu; Wang, Xiuheng; Bai, Shunwen; Xiang, Yue; Li, Lanqing
Abstract: Normalization and weighting are two life cycle impact assessment (LCIA) steps that are often uncertain and subjective. To make them more reliable, this article aims to contribute to the development of an up-to-date normalization reference (NR) and a better set of weighting factors (WF) for China through distance-to-target (DTT) weighting. In the present work, eight environmental criteria were assessed by policy targets, and the NRs of the contribution inventories were calculated. They included global warming (GW), ozone layer depletion (OD), acidification (Ac), eutrophication (Eu), photochemical oxidation (PO), abiotic depletion (fossil fuels) (ADF), freshwater aquatic ecotoxicity (FAET), and human toxicity (HT). Two WF sets with the target year of 2020 and 2030 were obtained; in both sets, GW had the highest relative importance and ADF had the lowest. Comparing the new WF sets with the WF sets of Europe and Thailand revealed the different emphasis of countries/regions with different development levels on environmental control. In addition, 1-kWh electricity generation was used as a case study to verify the differences and effects on the NR and WF results. This policy-based DTT method showed both strengths and weaknesses in the construction of Chinese WF sets. A clear policy based on every five-year plan would facilitate setting targets and simplifying data collation. Further attention needs to be paid to toxicity indicators, including the characterization factors for emerging pollutants such as new pesticides and policies on marine aquatic eco-toxicity and terrestrial eco-toxicity. Graphical abstract: Image 1 Highlights: The normalization reference set in LCIA for China in 2015 is calculated. Policy-based normalization reference sets in LCIA for China in 2020 and 2030 are forecasted. The weighting factor sets in LCIA are calculated based on the distance-to-target method. The critical environmental indicator is identified as ozone depletion in China during 2015–2020. Global warming is the most important and alarming environmental indicator in the coming future (2020–2030).